False-Positive 131I Uptake After Transareola Endoscopic Thyroidectomy in a Patient With Papillary Thyroid Carcinoma. (12th April 2022) - Wang, Anbo; Fu, Wenhui; Deng, Ying; He, Limeng; Zhang, Wei
Abstract: False-positive 131 I accumulation in patients with thyroid carcinoma could be due to various etiologies. Herein, we reported a case of papillary thyroid carcinoma in a 36-year-old woman. She underwent a 131 I radiotherapy after a transareola endoscopic total thyroidectomy. 131 I scintigraphy showed a high uptake in the thyroid bed. Surprisingly, increased activity was also noted in the right areola area. This activity corresponding to the entry site of endoscope revealed on the following SPECT/CT.